PERAN GANDA DAN PENGEMBANGAN KARIER GURU-GURU PEREMPUAN DI SEKOLAH MUHAMMADIYAH DI KOTA SURAKARTA - Chusniatun Chusniatun; Kuswardhani Kuswardhani; Joko Suwandi (Department of Accounting Education, Faculty of Teacher Training and Education Universitas, 2014)
The aims of this research gender are to describe; 1) The women teachers background at Muhammadiyah school – Surakarta have no ambition to be principal and 2) the relation with doubled role as house wife and teacher. The research subject is case study of women teachers at Muhammadiyah school-Surakarta. Data collection used is: in depth interview towards premmier sources and regarded to know their attitude carrier, while data analysis used Capacities and Vulnerabilities Analysis (CVA) technique. The research result showed that; 1)Women teachers background at Muhammadiyah school – Surakarta have no ambition to be principals, the reasons are; a) Carrier development system and principal candidates recruitment process is conducted by Dinas or foundation is not transparent; b) The role as house wife spend too much times and energy. 2) The conducting of doubled role of women teachers as house wife created role conflict in her profession, thus, structural carrier development did not do in good way.